Financial valuation of the German model: the negative relationship between ownership concentration and stock market returns, 1997-2001 - Clark, G; Wójcik, D (Clark University, MA, USA, 2005)
Believed to be a robust alternative to Anglo-American market capitalism, the virtues of the German model are increasingly disputed as doubts are raised about its long-term prospects. At the core of the German model is a system of corporate governance that is characterized by concentrated ownership and cross-holdings of stocks among related firms and their financial service providers. When combined with workers' representation on corporate supervisory boards, concentrated ownership is thought to encourage a longer-term competitive and investment strategy. Using a unique data set on German corporate voting rights and insights gleaned from intensive interviews with German and international financial institutions, we analyze daily stock market prices from 1997 to 2001, testing for the value attributed to concentrated ownership by financial markets. We show that the financial markets discount ownership concentration in ways that are consistent with Anglo-American conceptions of shareholder value, rather than with the logic of the German model. There is a significant negative relationship between ownership concentration and the average daily rate of return (as measured by closing stock market prices). This is an important finding for firms in the DAX100 and is the most pronounced for firms in the DAX30. Implications of these findings for the continued significance of distinctive regional systems of accumulation are considered in the final sections.